Initial results of the INSPIRE clinical trial—investigating radiation dosimetry for differentiated thyroid cancer patients - Taprogge, Jan; Abreu, Carla; Vávrová, Lenka; Carnegie-Peake, Lily; Rushforth, Dominic; Gape, Paul; Gear, Jonathan; Murray, Iain; Wong, Kee H.; Newbold, Kate; Yusuf, Siraj; Flux, Glenn (Frontiers in Nuclear Medicine, 2023)
Introduction The optimal strategy for differentiated thyroid cancer (DTC) patients treated with radioiodine (RAI) following thyroidectomy remains controversial. Multi-centre clinical studies are essential to identify strategies to improve patient outcomes while minimising treatment-induced toxicity. Materials and Methods The INSPIRE clinical trial (ClinicalTrials.gov Identifier: NCT04391244) aims to investigate patient-specific dosimetry for DTC patients and to determine the range of absorbed doses delivered to target and non-target tissues and their relationship with treatment outcome and toxicity. Results We report here initial results of the first 30 patients enrolled onto the INSPIRE trial. A large range of absorbed doses are observed for both thyroid remnants and salivary glands, with median values of 4.8 Gy (Range 0.2 – 242 Gy) and 0.3 Gy (Range 0.1 to 1.7 Gy), respectively. Discussion The preliminary study results are encouraging and could help to improve our understanding of absorbed doses to thyroid remnants and normal organs following RAI therapy. Such knowledge could potentially enable patient-specific treatment planning with improved clinical outcomes and quality-of-life of patients.